Socioeconomic Status and Livelihood Support Through Traditional Agroforestry Systems in Hill and Mountain Agro-ecosystems of Garhwal Himalaya, India - Bijalwan, Arvind; Sharma, Chandra Mohan; Kediyal, V. K. (Indian Forester, 2011)
The paper deals with the socioeconomic status and livelihood support through traditional agroforestry systems in Garhwal Himalaya, India. The predominant traditional agroforestry systems reported in the area were agrisilviculture (AS), agrihortisilviculture (AHS) and agrihorticulture (AH). A total 443 households were studied from the six selected villages with a family size of about 5.5 members per family. The adult literacy rate was 43% in marginal, 54% in small and 73% in medium-large land holding families while the child education rate was 86, 98 and 100%, respectively. The livestock were kept by 37 to 56% families in different villages. Each of these households has 2 to 4 milch animals and only 8 to 18% families kept oxen. The average daily fuel wood consumption during summer and winter in different villages varied from 84.41 to 538.45 kg/day/village and 156.75 to 701.01 kg/day/village which are supplemented by existing agroforestry upto considerable extent. The utilization of tree fodder varied from 305.02 to 1015.17 kg/day/village in the summer and 659.53 to 2015.52 kg/day/village in the winter season which is also supplemented by traditional agroforestry trees in a sizable limit. The land holding size ranged from 0.03 to 5.6 ha per family with 83.3% families were under marginal category, 14.7% under small category and 2.03% families comprised of medium-large landholding size. Agroforestry practice reported to be supportive and sustainable practice in this area with 20.24% monetary gain over sole cropping. The traditional agroforestry as such plays a significant role in the different facets of the household for their sustenance.